IMPLEMENTATION OF ANDROID APPLICATION TO SOLVE THE STUDENTS’ PRONUNCIATION OF ENDING –ED - M. Fadhly Farhy Abbas; Vina Fathira (English Review: Journal of English Education, 2020)
This research was done because of the students’ problem of pronouncing ending –ed. To solve the problem, the researchers tried to implement the application on learning media in this gadget era. The purpose of the research is to improve the students’ problem by implementing android application in pronouncing of ending –ed and to find the factors influencing the improvement. The method of this research was qualitative method. The research design was classroom action research of second-year-students in 2018/2019 academic year at STIBA (Foreign Language College) Persada Bunda Pekanbaru. The applications used were online and offline application English Pronunciation. The result showed that there is an improvement by implementing the android application of students’ pronunciation of ending –ed. It can be seen that the increasing of the students’ ability in pronouncing of ending –ed were at the level of “fairly good” category become the level of “good” category. Some factors influencing the students’ ability in pronouncing endng –ed were they often practice and listen to the android applications whether online and offline English Pronunciation to obtain the understanding and the information how to pronounce the exact words  of ending –ed. To conclude, the implementation of android application of online and android based can improve the ability of students’ pronunciation of pronouncing sound /t/, /d/, and /ɪd/ of ending –ed.